Literasi digital Sebagai Moderator WFH dan Produktivitas: Studi Kasus di UIN Sunan Ampel Surabaya - Ardianti, Cintia; Aji, Bramasta Kurnia; Rozas, Indri Sudanawati; Kunaefi, Anang (Systemic: Information System and Informatics Journal, 2025)
This study aims to explore the relationship between digital literacy and employee productivity during the COVID-19-induced work-from-home (WFH) scenario at UIN Sunan Ampel Surabaya. The government's social restrictions prompted the adoption of WFH strategies in higher education institutions. Utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS), a positive correlation was identified between WFH practices and employee productivity (path coefficient: 0.424). However, the impact of digital literacy on this correlation proved non-significant (path coefficient: -0.013, T Statistics: 0.258, P Values: 0.0796). These results emphasize the critical role of fostering digital literacy to elevate employee productivity in the WFH environment, offering valuable insights for organizations navigating remote work challenges